Evidence for the effectiveness of the Early Literacy Support programme - Hatcher, P; Goetz, K; Snowling, M; Hulme, C; Gibbs, S; Smith, G (2006)
Background. It is widely recognized that effective interventions for poor reading involve training in phoneme awareness and letter-sound knowledge, linked in the context of reading books. From the applied perspective, it is important to gather data on the effectiveness of different forms of implementation of literacy support within this framework. Aim. We evaluate the effectiveness of the UK Early Literacy Support (ELS) programme (Department for Education and Skills [DfES], 2001) relative to a programme of Reading Intervention based on 'sound linkage' (Hatcher, Hulme, and Ellis, 1994). Sample. The sample comprised 128 6-year-old children, from 16 primary schools in a Local Education Authority (LEA) in the north of England. Method. The children were nominated as in need of special help by their class teachers and allocated to one of the two programmes. Results. After controlling for a difference in spelling ability at the start of the intervention, it was found that both groups of children made equivalent and significant gains in reading and spelling that were maintained at follow-up. The standardized scores were in the average range. Regression analyses confirmed the importance of initial reading ability as well as letter identification, phoneme manipulation, and sound linkage in predicting progress in learning to read and to spell. Conclusion. The ELS programme provides a cost effective method of boosting 6-year-old children's reading to an average level. © 2006 The British Psychological Society.